Towards Customer Leadership - Campbell, Ian (Journal of Telecommunications and the Digital Economy, 2017)
Today Australia's telecommunications market is strongly contested. Competitors with highly skilled, experienced and focused marketing teams battle for market position, market share and profit growth.This has not always been so.Telecom Australia was established in 1975 as the government owned national telecommunications carrier. Protected by regulated monopolies for network services and customer  premises equipment, Telecom held perhaps 90% of the market. The predominantly engineering culture believed that it only needed a nominal marketing department and no sales force.In 1981 the monopolies were threatened. Telecom decided that it needed a sales force - quickly.This is a brief story of the building of that sales force over the first five years.In a government owned business steeped in the public service culture, strongly influenced by the public service unions and under a Labour government it was a grinding task.After five years the "subscribers" were more widely addressed and treated as "customers" and the sales force was operational. It was to be at least another six years before the sales force made the customers the focus of the business, and the skills, experience, management and culture of the force could match serious competitors in a de-regulated market.